Dependency as Ontology: Eastern Orthodox Reflections on Disability, Dependency, and Care - Karam McCray, Katherine (Zygon, 2025)
One of the fundamental hurdles for both Christian theology and medical ethics is characterizing disability as an aspect of human experience rather than a deviation from it. Anthropologies that anticipate a fixed subject articulate disability through the lens of pathology, alienating disabled experiences from what it means to be human. Pulling from the social theory of disability, I argue that wellbeing in Eastern Orthodox theology is characterized not by independent performative attainment but through mediated dependency. Eastern Orthodox theological anthropology organizes human dependency around passibility, an innate vulnerability that includes the ability to be acted upon as well as to suffer. Human nature comes packaged with material and social contingency. Christ’s passibility provides a moral framework through which extended states of dependency do not derive from sin or failure but rather serve as an example of quintessential human nature. Ontological dependency reframes persistent need, inviting persons who have been underserved and undervalued into a more inclusive model of human nature.